Enhancing Public Participation in Government-Operated Online Auctions: An Empirical Analysis of Purchase Intention Determinants on Lelang.go.id - Bima Agung Nugraha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of online auctions as part of the digital transformation of public services highlights the importance of studying the factors that influence users' purchase intentions towards government auction platforms, particularly lelang.go.id, in light of the relatively low level of public participation. By integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), this study aims to analyze the factors that shape users' purchase intentions on lelang.go.id by investigating the relationships between website design, trust, perceived ease of use, perceived usefulness, attitude, subjective norms, and perceived behavioral control on purchase intention, as well as testing the moderating role of perceived risk in the relationship between trust and purchase intention. A quantitative survey was conducted on 276 active users of lelang.go.id, and the data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The research results show that subjective norms, attitude, and perceived behavioral control have a significant direct influence on purchase intention, while trust does not have a direct influence but plays a role through perceptual mediation. Additionally, perceived risk was not proven to significantly moderate the relationship between trust and purchase intention. These findings underscore the importance of strategies to improve website design quality, information transparency, and the strengthening of trust and public perception to enhance the adoption of online auction systems.